E-058 High Resolution MRI and Pathological Evaluation of a Subacute Basilar Occlusion. (14th July 2013) - Burgess, R; Ching, E Cheng; Hussain, M; Toth, G; Bain, M
Abstract : Introduction/Purpose: Basilar occlusion is typically a devastating condition. The interventional treatment of only a handful of cases of sub-acute basilar thrombosis has been described in the literature. This report describes a case of basilar occlusion treated with delayed endovascular revascularisation studied with both high resolution MRI and surgical pathology evaluation. Materials and Methods: Case report and literature review. Historical, angiographic, high resolution MRI, and surgical pathological data will be presented. Results: A 73 year old male with rheumatic heart disease presented with blood pressure dependent dizziness, dysarthria, and right sided weakness. Workup revealed basilar occlusion above the left AICA with minimal leptomeningeal flow to the superior basilar segment, posterior cerebral and superior cerebellar arteries. The patient improved with, and thus was maintained on, IV vasopressor medications but could not be weaned from these medications after 8 days. High resolution MRI of the basilar segment was obtained. Endovascular revascularisation with mechanical thrombectomy (stent retriever) followed by stenting of the basilar artery was performed. The patient was neurologically stable after recanalisation despite return of blood pressure to baseline. Pathological evaluation of the removed thrombus was obtained. Conclusion: Endovascular recanalisation of a subacute basilar occlusion may be safely performed in a selected population. High resolution MRI may be a beneficial part of the pre-procedural evaluation of these case and other cases of subacute occlusion in patients with a low NIH stroke scale. Disclosures: R. Burgess: None. E. Cheng Ching: None. M. Hussain: None. G. Toth: None. M. Bain: None.